Hepatectomy for ruptured hepatocellular carcinoma classified as Barcelona Clinic Liver Cancer stage 0/A: The optimal treatment. Issue 9 (September 2022) - Xia, Feng; Huang, Zhiyuan; Zhang, Qiao; Ndhlovu, Elijah; Zhang, Mingyu; Chen, Xiaoping; Chen, Yifa; Zhang, Bixiang; Zhu, Peng
Abstract: Background and aims: Ruptured hepatocellular carcinoma (rHCC) generally has a very poor prognosis and is currently classified as T4 in the tumor–node–metastasis (TNM) staging system. In this study, we aimed to demonstrate the actual impact of rHCC, as well as the positive effect of hepatectomy in patients with Barcelona Clinic Liver Cancer (BCLC) stage 0/A rHCC. Methods: We enrolled 86 patients with rHCC after surgery and 526 patients with non-rHCC after surgery or transcatheter arterial chemoembolization (TACE). Survival curves were plotted using the Kaplan–Meier method to compare the postoperative prognosis of patients with rHCC with that of patients with non-rHCC. Univariate and multivariate Cox regression analyses were used to identify the risk factors affecting patient survival. Results: BCLC stage 0/A rHCC treated with surgery had a worse prognosis than BCLC stage 0/A non-rHCC treated with surgery (overall survival [OS]: hazard ratio [HR] = 3.12 [2.24–4.34], P < 0.001; recurrence-free survival [RFS]: HR = 2.26 [1.65–3.09], P < 0.001). Rupture was an independent prognostic factor in patients with BCLC stage 0/A rHCC (OS: HR = 1.685 [1.416–2.006], P < 0.001; RFS: HR = 1.484 [1.267–1.737], P < 0.001), and patients with BCLC stage 0/A rHCC who underwent surgery had a comparable prognosis to patients with BCLC stage B HCC who underwent surgery or TACE (OS: P = 0.78). Conclusions: Patients classified as having BCLC stage 0/A rHCC can achieve comparable outcomes to patients with BCLC stage B HCC after hepatectomy. However, not all patients with rHCC should be classified as T4 in the TNM staging system.